Medo, tensão e vergonha: representações negativas de sexualidade na seção sexo da revista Capricho - Pastana, Marcela; Maia, Ana Cláudia Bortolozzi [UNESP] (My University, 2012)
The magazines destined to the adolescent public are many times searched as a resource of information about sexuality, body, relationships and adolescence. The Capricho magazine is a biweekly feminine magazine directed to teenagers. In this qualitative-descriptive study it was made the content analysis of the section about sex of 18 editions published in 2010 with the aim of identifying and discussing the predominant representations of sexuality. It was identified the predominance of negative representations, like relations between sexuality and fear, tension, shame and beauty imperatives. It can be detached that the feminine sexuality is not approached through its pleasant, positive and health aspects, but through negative representations that, instead of being discussed, are naturalized, put as normal and expected by the magazine’s discourse.

As revistas destinadas ao público adolescente são muitas vezes procuradas como fonte de informações sobre sexualidade, corpo, relacionamentos e adolescência. A Revista Capricho é uma revista feminina quinzenal direcionada para adolescentes. Neste estudo qualitativo-descritivo foi realizada a análise de conteúdo da Seção “Sexo” de 18 edições publicadas em 2010 com o objetivo de identificar e discutir as representações predominantes sobre sexualidade. Foi identificada a predominância de representações negativas, como relações entre sexualidade e medo, tensão, vergonha e imperativos de beleza. Destaca-se como a sexualidade feminina não é abordada através de aspectos prazerosos, positivos e saudáveis, e sim através de representações negativas que, ao invés de discutidas e problematizadas, são naturalizadas, colocadas como normais e esperadas pelo discurso da revista.
Fear, tension and shame: negative representations of sexuality in the section about sex of the Capricho magazine
Keywords: Sexuality; Sexual repression; Adolescence; Normative patterns; Sexualidade; Repressão Sexual; Adolescência; Padrões Normativos